The Angle Degrees of the Grooves on the Lateral Sides of the Metatarsal Bones 234 for Identifying Them - Katkıcı, Ufuk; Gümüşburun, Erdem; Sevim, Ayla; Adıgüzel, Esat; Güleç, Erksin (The Bulletin of Legal Medicine, 1997)
A total of 403 metatarsal (MT) bones (184 second-SMT, 178 third-TMT, 141 fourth-FMT), were examined for the groove on the lateral side of the base. The values of the angles formed between the groove and the base were determined as 83°-115° for SMT, 57°-78° for TMT, 33°-55° for FMT respectively. The significance of the values of the angles was discussed for identification of the metatarsal bones.Key words: Anatomy, Metatarsal Bones, Identification.
Keywords: anatomy; metatarsal bones; identification